Iranian EFL university learners and lecturers’ attitude towards translation as a tool in reading comprehension considering background variables of age, major and years of experience - Sepideh Nourinezhad; Sara Kashefian-Naeeini (Cogent Education, 2020)
This study was conducted to examine the Iranian EFL university learners' and lecturers’ attitude towards translation as a tool in reading comprehension. A sample of 50 male and female students of Nursing, Medicine and 10 male and female lecturers at the Shiraz University of Medical Sciences were randomly selected. Using an Oxford Placement Test (OPT), the students in each field were homogenized. Two different questionnaires were administered. In the students’ questionnaire, items were about the functions of L1 in terms of translating in the EFL/ESL classroom based on, and the lecturers’ questionnaire included items about their attitudes towards L1 use in reading comprehension classes. It came to light that students of different age and major did not differ widely in their attitudes towards using translation in reading nor did lecturers differ in their opinions regarding the application of translation. Moreover, the results supported the effectiveness of using translation activities in L2 classrooms to improve student’s reading comprehension. This research is motivated by studies that suggest the use of L1 in ESL/EFL classroom can facilitate rather than impede target language learning.